Dukungan Keluarga dengan Kualitas Hidup - Seran, Benediktus; Anderson, Elisa; Manoppo, Arlien Jeannete (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Family support is the attitude and action of assisting the elderly by family members, so that the elderly will feel comfortable and have a good quality of life influenced by several factors such as physical, psychological, social, and environmental influenced by several factors such as physical, psychological, social, and environmental. This study aims to determine the relationship between family support and the quality of life of the elderly in Waleo Village. The research design used is descriptive correlation with a cross sectional approach. The research sample consisted of 114 elderly respondents aged 50-75 years through total sampling technique. The data collection instruments used were the family support questionnaire and the OPQOL-Brief adapted in Indonesian language. Most of the respondents had family support in the high category with 102 (89.5%) elderly, and quality of life in the good category with 109 (95.6%) elderly. Furthermore, the results of the Spearmen rank statistical test found a value of p = 0.000; and r = 0.400. There is a significant relationship between family support and the quality of life of the elderly in Waleo Village. The relationship is moderate in a positive direction, where the higher the family support, the higher the quality of life of the elderly. It is recommended that family members will continue to strengthen support for the elderly and continue to maintain it so that the quality of life for the elderly remains high and good. The elderly are also expected to continue to maintain a high quality of life by adding insight into health information. And for further researchers it is suggested to develop research by analyzing other factors that may affect family support and the quality of life of the elderly. Keywords: Family support, Quality of life, Elderly  ABSTRAK Dukungan keluarga adalah sikap dan tindakan mendampingi lansia yang dilakukan oleh anggota keluarga sehingga lansia merasa nyaman dan memiliki kualitas hidup yang baik dengan dipengaruhi oleh beberapa faktor seperti fisik, psikologi, sosial, dan lingkungan. Tujuan penelitian ini untuk mengetahui hubungan dukungan keluarga dengan kualitas hidup lansia di Desa Waleo. Desain penelitian yang digunakan adalah deskriptif korelasi dengan pendekatan secara cross sectional. Sampel penelitian sebanyak 114 responden lansia dengan umur 50-75 tahun melalui teknik pengumpulan data total sampling. Instrumen pengumpulan data yang digunakan adalah kuesioner dukungan keluarga dan OPQOL-Brief yang diadaptasi dalam Bahasa Indonesia. Sebagian besar responden memiliki dukungan keluarga pada kategori tinggi dengan jumlah 102 (89,5%) lansia, dan kualitas hidup pada kategori baik dengan jumlah 109 (95,6%) lansia. Selanjutnya, hasil uji statistik spearmen rank menemukan nilai p= 0,000; dan r = 0,400. Terdapat hubungan yang signifikan antara dukungan keluarga dengan kualitas hidup lansia di Desa Waleo. Hubungan bersifat sedang dengan arah positif, dimana semakin tinggi dukungan keluarga maka semakin tinggi kualitas hidup lansia. Diharapkan kepada anggota keluarga untuk tetap memperkuat dukungan pada lansia dan terus mempertahankannya agar kualitas hidup lansia tetap tinggi dan tetap bagus. lansia juga diharapkan dapat terus mempertahankan kualitas hidup yang tinggi dengan menambah wawasan tentang informasi kesehatan. Dan untuk peneliti selanjutnya disarankan untuk mengembangkan penelitian dengan menganalisis faktor-faktor lain yang dapat mempengaruhi dukungan keluarga dengan kualitas hidup lansia.  Kata Kunci: Dukungan keluarga, Kualitas Hidup, Lansia